Flood Disaster Response Cadre Training in Keliling Benteng Ulu Village, Martapura Barat Sub-District - Fujiati; Nelly Al Audhah; Dwi Setyohadi; Endah Labati Silapurna; Abrari Fauzi; Brian Pramana Santoso; Marcellino Febryan; William Luth; Sayid Akhmad Zein; Irawanto (Asian Journal of Community Services, 2023)
A flood is an event where land is submerged due to an increase in water volume. The flood that occurred in RT.05 Keliling Benteng Ulu Village was the worst compared to other RTs, because they live on the edge of the Martapura river and swamp environment. This service activity educates cadres to fulfill basic needs (clean water and sanitation needs, food clothing, temporary shelter, and health services) and provides leaflets/booklets on the stages of flood disaster management in fulfilling the basic needs of the community. The results of the pre and post test evaluation, cadres' knowledge has increased ≥ 80% regarding flood disaster response and about fulfilling the basic needs of flood disaster management independently (making freshwater fish jerky and instant ginger).